Altered Membrane Properties and Firing Patterns of External Globus Pallidus Neurons in the R6/2 Mouse Model of Huntington’s disease - Akopian, Garnik (J Neurosci Res, 2016)
In mouse models of Huntington’s disease (HD), striatal neuron properties are significantly altered. These alterations predict changes in striatal output regions. However, little is known about alterations in those regions. In the present study we examined changes in passive and active membrane properties of neurons in the external globus pallidus (GPe), the first relay station of the indirect pathway, in the R6/2 mouse model of juvenile HD at pre- (1 mo) and symptomatic (2 mo) stages. In GPe, two principal types of neurons can be distinguished based on firing properties and the presence (type A) or absence (type B) of I(h) currents. In symptomatic animals (2 mo), cell membrane capacitance and input resistance of type A neurons were increased compared to controls. In addition, action potential after-hyperpolarization amplitude was reduced. Although the spontaneous firing rate of GPe neurons was not different between control and R6/2 mice, the number of spikes evoked by depolarizing current pulses was significantly reduced in symptomatic R6/2 animals. In addition, these changes were accompanied by altered firing patterns evidenced by increased inter-spike interval variation and increased number of bursts. Blockade of GABA(A) receptors facilitated bursting activity in R6/2 mice but not in control littermates. Thus, alterations in firing patterns could be caused by changes in intrinsic membrane conductances and modulated by synaptic inputs.